Climate Change, Disaster Risk Reduction and Gender: The Southeast Asia Experience - Sembiring, Margareth (2016)
The 2005 Hyogo Framework for Action has called for a gendered approach in disaster risk reduction efforts. Despite being frequently battered by climate-related disaster events, countries in Southeast Asia remain rather slow in mainstreaming gender in their disaster management policies and action plans.